2005
DOI: 10.1002/rcm.2310
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification of N‐acetylheparosan oligosaccharides by tandem mass spectrometric fragmentation

Abstract: Recently, a useful procedure for the preparation of both even- and odd-numbered series of N-acetylheparosan (NAH) oligosaccharides was established. The present report describes findings when these NAH oligosaccharides were subjected to comparative mass spectrometry (MS)/MS fragmentation analysis by matrix-assisted laser desorption/ionization (MALDI)-LIFT-time-of-flight (TOF)/TOF-MS/MS, and electrospray ionization (ESI) collision-induced dissociation (CID) MS/MS. The resultant fragment ions were systematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Some fractions contained HPR heptasaccharide (HPR-7). The structures of the oligosaccharides were determined by MALDI-TOF mass spectrometry and electrospray ionization-mass spectrometry analyses (17). The amount of HPR oligo-and polysaccharides was determined by carbazole assay method with GlcUA monosaccharide as standard (18).…”
Section: Methodsmentioning
confidence: 99%
“…Some fractions contained HPR heptasaccharide (HPR-7). The structures of the oligosaccharides were determined by MALDI-TOF mass spectrometry and electrospray ionization-mass spectrometry analyses (17). The amount of HPR oligo-and polysaccharides was determined by carbazole assay method with GlcUA monosaccharide as standard (18).…”
Section: Methodsmentioning
confidence: 99%
“…The number "−2" designates deprotonation (−2H) accompanied with cleavage of the glycosidic bond because proton transfer occurs at Z and B fragment formation in the negative ion mode (mass shift rule) [29]. The m/z values observed for fragment ions between C and Y fragments having the same sugar length from saturated free oligosaccharide of nonsulfated GAG and for fragment ions between C and Z fragments from unsaturated free oligosaccharides were the same [27,30]. All the observed fragments from PA-CH oligosaccharides were distinguished from each other due to the presence of aglycon PA at their reducing ends.…”
Section: Maldi-lift-tof/tof Ms/ms Analysis Of the Pa-ch Oligosaccharidesmentioning
confidence: 80%
“…3). Ion-source decay (ISD) fragment ions that often appeared in the spectra of underivatized GAG oligosaccharides [27] were rarely observed in PA-CH oligosaccharides, since the laser power required for ionization of PA-CH oligosaccharides was substantially lower than that for ionization of the corresponding underivatized CH oligosaccharides,.…”
Section: Maldi-tof Ms Analysis Of the Pa-ch Oligosaccharidesmentioning
confidence: 99%
“…Figure 3 and Table 3 show the results including that for NAH tetrasaccharide (DNAH4). 23) As in the case of saturated forms, C 3 ions (m/z 554) were produced for DCH4 and DHA4 most intensely. This demonstrated that this glycosidic linkage had been most fragile in the structure of the series.…”
Section: Unsaturated Tetrasaccharidesmentioning
confidence: 89%
“…22), 23) The fragmentation behavior observed was unique, reflecting the alternating HexA῍HexNAc sequence, as well as the glycosidic linkage position. 23) This prompted us to confirm MS potentiality to di#erentiate structural isomers of NAH oligosaccharides.…”
Section: Introductionmentioning
confidence: 97%